BENEFIT AND LOSES OF TIN SALES PB 300 TROUGH AN INTERNATIONAL COMMODITY EXCHANGES (CASE: TIN EXPORTER COMPANY IN INDONESIA) - Hartono, Yurika Listiyani; Praja, Arief Kusuma Among (Universitas Esa Unggul, 2016)
Abstract International trade is divided into two types of export and import. Indonesia because of its natural resources has the potential to perform the export of tin to fulfilled the needs of the worlds tin. The Company utilizes the position of Indonesia as tin-best world to do business internationally. Every business must be have a risk, as well as international business. Macroeconomics usually affect on this business sector like the exchange rate and prices. This thesis aims to analyze the influence of LME price, exchange rate and CPI on profit earned by the company by sales trading through an international exchange market ICDX (Indonesia Commodity and Derivatives Exchange). This study uses information trading sales which made by the company during the start operation. The study was conducted with a descriptive design causality, data analysis performed using ANKOVA test with one covariate and to prove the relationship between variables was tested using granger causality test. Research to obtain the result that LME price which moderated by exchange rate and CPI covariate affecting company profit significantly, the results reinforced the granger causality test results that support of the research hypothesis. From these results the company is expected to determine a better strategy in order to compete with similar companies that already exist and can improve the positioning of the company in the tin market. So that the company can obtain pay a high enough price from the buyer. The company is also expected to improve the ability of bargaining with the buyer in determining the settlement payment in order to be more profitable company.Â Keyword: Trading, exchange rate, settlement, international exchange stocks.